2023
DOI: 10.3389/fimmu.2023.1135930
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 alleviates inflammation in ulcerative colitis by activating the VDR-NLRP6 signaling pathway

Abstract: Inflammation is a key factor in the development of ulcerative colitis (UC). 1,25-dihydroxyvitamin D3 (1,25(OH)2D3, VD3), as the major active ingredient of vitamin D and an anti-inflammatory activator, is closely related to the initiation and development of UC, but its regulatory mechanism remains unclear. In this study, we carried out histological and physiological analyses in UC patients and UC mice. RNA sequencing (RNA-seq), assays for transposase-accessible chromatin with high-throughput sequencing (ATAC-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…Gao H et al, 2023 found that vitamin D supplementation alleviates inflammation in ulcerative colitis, and provided evidence for the use of vitamin D in the clinical treatment of ulcerative colitis [28]. This is in line with our suggestions, according to the significance of our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gao H et al, 2023 found that vitamin D supplementation alleviates inflammation in ulcerative colitis, and provided evidence for the use of vitamin D in the clinical treatment of ulcerative colitis [28]. This is in line with our suggestions, according to the significance of our results.…”
Section: Discussionsupporting
confidence: 92%
“…Considering our results, as well as the results of previous studies, which confirm the effects of vitamin D supplementation in suppressing inflammation [28][29][30], the analysis of VD status and vitamin D supplementation during treatment of IBD is recommended.…”
Section: Discussionsupporting
confidence: 82%
“…Copper is an indispensable trace metal element in the human body, actively participating in energy production, iron metabolism, neuropeptide activation, connective tissue synthesis, and neurotransmitter synthesis. [6] Extensive research indicates that copper, serving as a cofactor for various crucial metabolic enzymes, is a vital component of the body's defense system, driving a wide array of physiological processes. [6,7] Involving multiple copper transport proteins and their regulation, both shallow and high copper levels have been shown to lead to cell death.…”
Section: Copper Metabolism and Homeostasismentioning
confidence: 99%
“…[6] Extensive research indicates that copper, serving as a cofactor for various crucial metabolic enzymes, is a vital component of the body's defense system, driving a wide array of physiological processes. [6,7] Involving multiple copper transport proteins and their regulation, both shallow and high copper levels have been shown to lead to cell death. Thus, maintaining copper levels within an appropriate range is essential.…”
Section: Copper Metabolism and Homeostasismentioning
confidence: 99%
“…Because vitamin D plays a role in modulating the immune system [23][24][25][26], we hypothesized that patients who have a high baseline vitamin D level of ≥30 ng/mL at the initiation of vedolizumab would have the best clinical and endoscopic responses to therapy. This vitamin D level is based on the classifications of normal, insufficient, and deficient levels of vitamin D [27].…”
Section: Introductionmentioning
confidence: 99%